Current development of creep-resistant magnesium cast alloys: A review. (5th October 2018) - Mo, Ning; Tan, Qiyang; Bermingham, Michael; Huang, Yuanding; Dieringa, Hajo; Hort, Norbert; Zhang, Ming-Xing
Abstract: The low creep resistance has been one of the major issues of Mg alloys, which limited their wider industrial applications in the past decades. It has been reported that the inherent creep resistance of Mg should be higher than that Al. Hence, it is highly likely that the low creep resistance of Mg alloys was attributed to the effects of alloying elements rather than Mg itself. In order to systematically understand the effects of alloying elements on the creep behaviours of cast Mg alloys and therefore to develop new alloys with higher creep resistance, the present work reviews the major creep-resistant Mg systems that were developed and successfully commercialized for applications at different temperatures. Because the majority of commercial Mg alloys are used as cast, this review focuses on cast alloys. Graphical abstract: Unlabelled Image Highlights: The creep behaviour of major creep-resistant Mg systems is reviewed. The effect of various alloying elements on creep behaviours is discussed. The strengthening mechanisms to creep resistance of Mg alloys are discussed.